The "Psychosocial Determinants of Life Satisfaction in Patients with Hepatitis b and Hepatitis C: "Psychosocial Determinants of Life Satisfaction in Patients with Hepatitis b and Hepatitis C - Rasheed, maham; Yasmeen, Sumaira; Ali, Syed Messum (Journal of Peace, Development and Communication, 2022)
Aim: The purpose of the present study was to assess the role of grit, metacognitive awareness and depression in life satisfaction of patients with Hepatitis B and Hepatitis C. It was hypothesized that these constructs would be significantly associated with one another, specifically, that depression would negatively predict life satisfaction while grit and metacognitive awareness would have positive associations with life satisfaction. Method: The study used a correlational research design. The sample size of the study was 200 including (N=120 males, N= 80 females) diagnosed with hepatitis b and hepatitis c and selected from various healthcare settings in Lahore. The purposive sampling technique was used for sample selection. Beck Depression Inventory, Short Grit Scale, Satisfaction with Life Scale, and Metacognitive Awareness Inventory were used for data collection. Result: The results showed that grit and metacognitive awareness is positively associated with life satisfaction while depression has a significant negative association. There were no gender differences among the patients on the constructs. Depression and Metacognitive Awareness significantly predicted life satisfaction among the patients. Depression and metacognitive awareness were found as having a negative and positive mediating influence respectively on the association between grit and life satisfaction. Keywords: Grit, Depression, Metacognitive Awareness, Life Satisfaction, Hepatitis B and Hepatitis C